2016
DOI: 10.1016/j.triboint.2016.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and tribological behavior of aluminum matrix composites reinforced with in-situ AlB2 particles

Abstract: . (2016). Mechanical properties and tribological behavior of aluminum matrix composites reinforced with in-situ AlB 2 particles. Tribology International, 98 41-47. Mechanical properties and tribological behavior of aluminum matrix composites reinforced with in-situ AlB2 particles AbstractAluminum matrix composites (AMCs) reinforced with in-situ AlB 2 particles have been fabricated using a combination of powder metallurgy, hot rolling and solution treatment. The effects of boron content (7 and 12 wt%), hot roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(28 citation statements)
references
References 46 publications
2
24
0
2
Order By: Relevance
“…Such hardness improvement results from effective load transfer between the aluminum matrix and the reinforced AlB 12 particles, as previously demonstrated in aluminum-based composites containing B 4 C particles [15,16]. AlB 12 particles tend to organize themselves in clusters when surrounded by liquid aluminum, as indicated in previous works, attributed to the lack of sufficient mixing (stirring) when the matrix was molten [17]. e same behavior occurred in our experiments due to the short melting time upon sample fabrication.…”
Section: Optical Microscopysupporting
confidence: 89%
“…Such hardness improvement results from effective load transfer between the aluminum matrix and the reinforced AlB 12 particles, as previously demonstrated in aluminum-based composites containing B 4 C particles [15,16]. AlB 12 particles tend to organize themselves in clusters when surrounded by liquid aluminum, as indicated in previous works, attributed to the lack of sufficient mixing (stirring) when the matrix was molten [17]. e same behavior occurred in our experiments due to the short melting time upon sample fabrication.…”
Section: Optical Microscopysupporting
confidence: 89%
“…The wear properties of the hybrid composites containing graphite exhibited the superior wear resistance properties. Linlin et al [18] investigated mechanical and tribological behavior of aluminium metal matrix composites reinforced with in situ AlB 2 particles. Composites were prepared by hot rolling and solution treatment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rahman et al, reported tha the incorporation of varying weight percentage (0,5 ,10, & 20 Wt.%) of silicon carbide in aluminum matrix material synthesized by using stir casting process led to strengthen the alumina-SiC composites [12]. Yuan et al, reported that increase in weigth percentage of Boron content led to agglomeration and uneven distribution of boron in Al matrix and also coccluded that Al with 7 Wt.% of Boron has given better yield and tensile strength of Al-Boron composites [13]. Various ceramical reinforcement such as Silicon Carbide having density 3.2 g/cc and hardness 2600 HV.…”
Section: Introductionmentioning
confidence: 99%